PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PENGUNJUNG BERKUNJUNG KE MUSEUM NASIONAL - Revalino Tigor Hasudungan; Lut Mafrudoh (Eduturisma, 2020)
In the history of museums development, there have been changes the character of changing the function of the museum which initially then developed and increased with the function of preserving, preserving, presenting, or exhibiting, and finally, this function increased. The purpose of this study were: a) to determine the effect of product quality on visiting decisions to the National Museum, b) the influence of location on the visiting decision to the National Museum. This research used multiple linear regression analysis method and incidental sampling method get the respondents. The sampling criteria were visitors who came only on Tuesday – Saturday. The study found that the higher the product quality is, the visiting decision increases. It was explained that the product quality has a significant effect on visiting decisions. The location also has a significant effect on purchasing decisions. The better location of the museum is increasing the visitors decision. The location also shows a significant influence on purchasing decisions.